Incidental findings of isolated colonic varices at the hepatic flexure due to pancreatic head and uncinate process cancer: a case report - Kang, Inmo (Kosin Medical Journal (Online), 2025)
In cases of portal hypertension, collateral pathways may form to bypass the obstruction or resistance. These pathways can create ectopic varices at various sites along the gastrointestinal tract in addition to the common gastroesophageal region. Among these, colonic varices are a particularly rare subtype. Colonic varices can develop owing to conditions such as portal hypertension, splenic or portal vein thrombosis, and mesenteric vein obstruction. This report presents a case of incidental colonic varices at the hepatic flexure, which led to the diagnosis of cancer in the pancreatic head and uncinate process.